Իրաքում Ճապոնիայի ռազմական ներկայության վերաբերյալ - Կարապետյան, Ռուբեն («Զանգակ - 97»)
The article provides Short background on Japanese Seif Dcfencc Forces and what lies hehind lhc dccision of lhc Japanese govcrnmcnl Tor sending its small military conlingcnt lo Irag in Fcbruary 2004. By sending lhe iroops lo Iraq Tokyo is trying to rejoin the ranks of lhc greal powers and play a full-fledgcd security role not only in lhc region bul on the wider worid slage. Taking into consideration the substantial changcs in the Japanese l'oreign political agenda, a new approach to lhe whole system of Armenian-Japancsc bilateral relations is required.
Keywords: Պատմություն; Քաղաքականություն